Comparison of Milrinone with Sildenafil for the Treatment of Persistent Pulmonary Hypertension of the Newborn - Imtiaz Ahmad; Motia Javaid; Tanveer Ahmad; Imran Baloch; Nisar Khan Sajid; Abdul Razzaq Mughal (Journal of Aziz Fatimah Medical and Dental College)
Objective: To compare milrinone with sildenafil for the treatment of persistent pulmonary hypertension of the newborn.